Making an ultralow platinum content bimetallic catalyst on carbon fibres for electro-oxidation of ammonia in wastewater. Issue 8 (20th June 2019) - Pourrahimi, A. M.; Andersson, R. L.; Tjus, K.; Ström, V.; Björk, A.; Olsson, R. T.
Abstract : Conductive high surface area carbon fibres with a bimetallic copper–platinum coating are used as electrode for electro-oxidation of wastewater ammonia. The metal alloy is presented as a novel inexpensive catalyst for the generation of hydrogen gas. Abstract : Electrocatalysis of wastewater containing ammonia is a promising alternative to chemical and biological water purification for several reasons, one being that energy-rich hydrogen gas is generated as a by-product while the reaction can be strictly controlled to meet demands. An objective has been to reduce the loading of expensive platinum (Pt) in the catalyst electrodes, and to reduce the poisoning of the metal surface during the electrolysis. Herein, the co-deposition of a copper–platinum (Cu–Pt) bimetallic alloy onto carbon filaments, stripped from their polymeric coating, is shown to give an electrocatalytic performance superior to that of pure Pt at a content of less than 3 wt% Pt. The key to the enhanced performance was to take advantage of micrometer-sized carbon filaments to distribute a very large bimetallic alloy surface uniformly over the filaments. The Cu–Pt-alloy-coated filaments also suffer less electrode poisoning than pure Pt, and are bonded more strongly to the carbon fibre due to better mechanical interlocking between the bimetallic alloy and the carbon filaments. High-resolution electron microscopy studies combined with a tuned electro-deposition process made it possible to tailor the catalyst micro/nano morphology to reach a uniform coverage, surrounding the entire carbon filaments. The results are promising steps towards large-scale wastewater treatment, combined with clean energy production from regenerated hydrogen.